Prevalence of Vigabatrin-Induced Visual Field Loss - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
The magnitude of risk of vigabatrin-associated visual field loss and any clinical predictors of risk were determined by systematic review of 32 studies identified by electronic searches of the literature.